2004
DOI: 10.1673/031.004.1601
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific competition in the speckled wood butterfly Pararge aegeria: Effect of rearing density and gender on larval life history

Abstract: In insects, the outcome of intraspecific competition for food during development depends primarily upon larval density and larval sex, but effects will also depend on the particular trait under consideration and the species under study. Experimental manipulations of larval densities of a Madeiran population of the speckled wood butterfly Pararge aegeria confirmed that intraspecific competition affected growth. As densities increased P. aegeria adults were smaller and larval development periods were longer. Sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 50 publications
2
33
0
1
Order By: Relevance
“…Females can potentially use cues other than their own mating status to adjust signaling effort: if females can perceive the signals of competing females, there is potential for more complex signaling strategies than the ones modeled by us (Harari et al 2011). Experimental manipulation of juvenile environments can also prove informative (Gibbs et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Females can potentially use cues other than their own mating status to adjust signaling effort: if females can perceive the signals of competing females, there is potential for more complex signaling strategies than the ones modeled by us (Harari et al 2011). Experimental manipulation of juvenile environments can also prove informative (Gibbs et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Under conditions of restricted food supply, many lepidopteran larvae extend their development and consequently their feeding period in order to attain a critical size for metamorphosis (Fischer & Fiedler, 2001;Bauerfeind & Fischer, 2005). In addition, larval crowding during development causes a reduction in female pupal and adult weight in a number of species (Leonard, 1968;Peters & Barbosa, 1977;Fisher & Fiedler, 2001;Agnew et al, 2002;Gibbs et al, 2004). However, the results of these studies are contradictory, so it is unclear whether these effects are caused by the group density per se or by the reduced availability of food.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of these studies are contradictory, so it is unclear whether these effects are caused by the group density per se or by the reduced availability of food. In Pararge aegeria (L.) for example, high larval crowding resulted in lower survival and a longer developmental period (Gibbs et al, 2004). Tammaru et al (2000) found that crowding during early larval development strongly delayed larval growth in Epirrita autumnata and reduced pupal weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Griffith and Poulson 1993), wood butterfly (cf. Gibbsac et al 2004) also used to take part in intraspecific competition. The intraspecific competition among prey is incorporated in the model through the theta-logistic growth rate of prey.…”
Section: Discussionmentioning
confidence: 99%